Dydaktyka i wychowanie w szkołach wiejskich w okresie dwudziestolecia międzywojennego na przykładzie szkół powszechnych gminy Garbów - Makarewicz, Renata (Biuletyn Historii Wychowania, 2016)
The aim of this article is to present the processes of education and upbringing in the curricula for universal schools in the Interwar Period. In the article, the example of primary schools is cited, operating in Garbów commune and the structure of the primary school network is described together with financial and material problems experienced in these schools and the methods of overcoming them. The teaching work of the teachers is presented with emphasis placed on the activity of school institutions and students organizations in the area. Attention is also paid to the significance of the achievements of the teaching and upbringing methods applied in primary schools in the Interwar Period. The article is based on information obtained from sources made available by the National Archives in Lublin and chronicles stored in schools still operating in Garbów commune.